Gelatin-Modified Polyurethanes for Soft Tissue Scaffold. (20th November 2013) - Kucińska-Lipka, Justyna; Gubańska, Iga; Janik, Helena
Abstract : Recently, in the field of biomaterials for soft tissue scaffolds, the interest of their modification with natural polymersis growing. Synthetic polymers are often tough, and many of them do not possess fine biocompatibility. On the other hand, natural polymers are biocompatible but weak when used alone. The combination of natural and synthetic polymers gives the suitable properties for tissue engineering requirements. In our study, we modified gelatin synthetic polyurethanes prepared from polyester poly(ethylene-butylene adipate) (PEBA), aliphatic 1, 6-hexamethylene diisocyanate (HDI), and two different chain extenders 1, 4-butanediol (BDO) or 1-ethoxy-2-(2-hydroxyethoxy)ethanol (EHEE). From a chemical point of view, we replaced expensive components for building PU, such as 2, 6-diisocyanato methyl caproate (LDI) and 1, 4-diisocyanatobutane (BDI), with cost-effective HDI. The gelatin was added in situ (in the first step of synthesis) to polyurethane to increase biocompatibility and biodegradability of the obtained material. It appeared that the obtained gelatin-modified PU foams, in which chain extender was BDO, had enhanced interactions with media and their hydrolytic degradation profile was also improved for tissue engineering application. Furthermore, the gelatin introduction had positive impact on gelatin-modified PU foams by increasing their hemocompatibility.